HVOF deposition characteristics and corrosion resistance of 316 stainless steel coating on magnesium alloy surface - LI Xuqiang; LI Wensheng; ZHANG Zheyun; CUI Shuai; SHAO Lei; ZHAI Haimin (Cailiao gongcheng)
The 316 stainless steel coatings with different thicknesses （SSC2， SSC4， SSC7， SSC10） were deposited on the magnesium alloy surface by using the HVOF method. The microstructures， deposition characteristics， residual stresses and immersion corrosion characteristics of the coating were investigated. The results reveal that due to the lower melting point and hardness of magnesium alloy， spray particles are prone to invade the substrate and melt its surface， causing particle escape or splashing， resulting in lower deposition efficiency； after depositing thinner coatings （SSC2 and SSC4）， the escape or splashing behavior of deposited particles reduces significantly， and the deposition efficiency increases； when the deposition thickness increases to SSC7 or above， the surface temperature of the deposition increases， particle splashing gradually increases， and the porosity and oxide content of the coating surface increase. Furthermore， as the coating thickness increases， the residual compressive stress of the coating decreases， the stress distribution becomes more uniform， and the number of penetrating pores in the coating decreases significantly， approaching zero. There are penetrating pores inside the SSC2 and SSC4 coatings， and the effective protection time is extremely short. The thick coatings （SSC7 and above） still have a protective effect after soaking in 3.5% （mass fraction） NaCl solution for 720 h.